Teacher emotion and pedagogical decision-making in ESP teaching in a Chinese University - Zhao, Hua; Li, Danli; Zhong, Yong (Frontiers in Psychology, 2022)
Teacher emotion, a crucial construct in understanding teachers’ responses to institutional policies, has taken on an increasing important role in English language teaching. The study explored teachers’ emotion labor and its impact on teachers’ pedagogical decision-making in English for Specific Purposes (ESP) teaching in a university of Traditional Chinese Medicine (TCM) in China. Drawing on a poststructural perspective, the study examined data from two rounds of semi-structured interviews, policy documents and teaching artifacts. The analysis of data revealed that the major emotion labor facing the participants revolved around students’ disengagement in class. Teachers experienced mixed feelings of anticipation, disappointment, anger, and empathy towards students and distanced themselves from institutional feeling rules enforcing objective assessment of students’ performance and punishing students for lack of engagement in class. The study found that teacher emotion labor served as the site for their pedagogical modifications. ESP teachers’ beliefs in the importance of attending to students’ needs become a powerful discourse in supporting teachers to strategically subvert institutional feeling rules and critically reflect on the dysfunctions of curriculum, orienting teachers’ agentic actions in modifying pedagogical practices. We thus underscore this empowering discourse as the bridge to connect teachers’ policy negotiation and their actual classroom practices. We also highlight teachers’ pedagogical decision-making as a process of the interactions of teacher emotion, teachers’ reflexive practices, and power relations. The study ended by suggesting more longitudinal research where teachers’ beliefs as previously appropriated discourses could be examined comprehensively as they were both the construct of emotion labor and the potential subverting power in supporting teachers’ pedagogical decision-making in policy negotiation.